Denmark : Systemic Issues in Mortgage Loans and Covered Bond Finance: Technical Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This technical note analyzes systemic issues in mortgage loans and covered bond finance in Denmark. Mortgage lending has seen significant product innovation in recent years. Loans with adjustable interest rates and/or interest-only periods, which have been introduced since the late 1990s, had grown to 75 percent and 53 percent, respectively, of total outstanding mortgage loans at the end of 2013. The major changes in the characteristics of the underlying mortgage loans have naturally been reflected in an important evolution of the covered bond market. Traditionally, covered bonds were callable annuities with maturities closely matching those of the underlying fixed rate loans. In contrast, adjustable and variable interest rate loans are financed by bonds with short maturities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet